Pengaruh Broadcasting Youtube Terhadap Minat Wisatawan Berkunjung di Pantai Parangtritis Bantul DIY - Yuliantoharinugroho, Yuliantoharinugroho; Subandi, Subandi; Rofik, Mochamad; Fadilah, Khaeratul (Universitas Medan Area, 2023)
The aim of this research is to determine the influence of YouTube broadcasting on tourists' interest in visiting Parangtritis Beach, Bantul Regency, DIY. This research is a type of quantitative research and data collection techniques use questionnaires, observation, literature study and documentation. The population of this research is the number of visitors to Parangtritis Beach in 2022 who have seen broadcasts related to Parangtritis Beach on the social media accounts of the Bantul Regency Tourism Office. Sample selection was carried out using purposive nonprobability sampling. The sample used was 100 tourists. The research results show that YouTube broadcasting has a significant effect on tourists' interest in visiting Parangtritis Beach with a t count of 6.890, significance 0.000 0.05.